Investigating the bioremediation of heavy metals by Pleurotus ostratus - Fereshteh Mohamadhasani Javar; Mehdi Rahimi (یافته‌های نوین در علوم زیستی, 2023)
Heavy metal contamination (HMs) of water and soil is the most serious problem caused by industrial and mining processes and other human activities. Mycoremediation is a biotechnological method that employs fungi to remove toxic contaminants from the environment in an efficient and cost-effective manner. Pleurotus species are considered to be the most popular and widely cultivated species worldwide, and this may be due to their low production cost and high yield. It has been indicated that Pleurotus species may improve plant growth in metal-contaminated soils through enhancing nutrition uptake or by alleviating toxicity of the metals. In this experiment, the fungus was grown in vitro in liquid and solid media for 3 weeks on five different concentrations (0, 15, 30, 45, 60 ppm) of five heavy metals (Cd, Zn, Ni, Pb, Mn) as sulphate and the effect of these metal on radial growth, biomass production and metal content of fungal biomass were determined. Based on the results, this fungus showed a great variety of tolerance against the metals, as that growth parameters were increased in the case of two metals contamination (Zn and Mn) and inhibition of growth was observed even at the low concentrations of nickel, cadmium and lead (15 mg/liter). The amount of metal accumulation in the fungal mycelium also increased with the increase of the metal concentration in the culture medium. In this research, for the first time, the growth parameters and the amount of accumulation of heavy metals in axenic conditions have been investigated and described.